Light steel framing façades: mechanical behavior of cementitious boards and numerical structural modeling for high building applications. - Boriolo, Gustavo Rodovalho (2021)
This work presents a framework to assess the mechanical behavior of lightweight façades in high buildings. This framework is based on the definition of a set of structural requirements for the steel frame structure, the fiber cement boards and their fixing system. These requirements have been proposed and verified considering both the ultimate and the serviceability limit states (ULS and SLS), and differentiating the global and local structural behaviors under wind loads action and hygrothermal dimensional variations. Design wind loads have been proposed based on a documental comparison of different international standards for wind action on buildings. The behavior of the boards and the screws was experimentally characterized in different conditions of humidity and aging. Several finite element models were created in ABAQUS to simulate the materials behavior and to predict the mechanical performance of the façade system. It has been verified that aging improves the ultimate strength of the fiber cement material, also moisture changes this material behavior by rising its ductility and degrading its final strength. The modeling strategy has been proven to be capable to provide decent results to predict the façade performance. It has been demonstrated that the XFEM and the Hashin bi-linear models have limits to simulate a fiber cement board. Moreover, the Concrete Damage Plasticity has been confirmed as a convenient formulation to capture the cracking mechanisms of the board, having a good fit, even in the post-peak behavior. The numerical results have shown that the fixing system definition is crucial to prevent cracks. Minimum edge distances must be respected to mitigate these risks, and the use of pre-drilling is helpful to avoid any stress concentration due to shrinkage. Numerical simulations have also been performed to define an optimized configuration for a 30-floor building façade considering a critical wind load. These simulations, in a specific and illustrative case, have resulted in studs of 200mm spaced at each 400mm and with non-winged screws at each 400mm.